Characteristic Factors of Health Micro Insurance Against Considerations in Selection of Health Service Facilities - Radya Pratiwi Serila; Dwi Susanti; Riaman Riaman (International Journal of Research in Community Services, 2023)
Indonesia is still faced with a series of health problems. One of the causes of health problems is the expensive cost of treatment.  An alternative that people can choose for health financing is to have health micro-insurance aimed at lower-middle-class households. The purpose of this study was to identify factors characteristic of micro-insurance, against the consideration of choosing health service facilities. The data used were primary data obtained through a questionnaire of 220 health micro-insurance participants. This research was analyzed with a quantitative descriptive approach. The results of the analysis show that the characteristics of hospitals that are registered as good quality micro-insurance services and responsive to providing referrals to hospitals, when there are patient complaints are the main factors in considering the choice of health service facilities.